THE STUDY OF THE SELECTION OF FISHING GROUND BASED ON SEA SURFACE TEMPERATURE AND KLOROFIL-a IN THE ASAHAN OCEAN WATERS BY USING SATELLITE IMAGES AQUA MODIS - Tamba, Marlan; Ghalib, Musrifin; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study was conducted in October 2015 in Asahan waters NorthSumatera. The aim of this research is to know the fishing ground in Asahanwaters based on conditions of sea surface temperature and chlorophyll-aabundance by using Satellite Images Aqua Modis. Methods used in this researchis survey method and a visual analysis Aqua Satellite Images Modis. The resultsof the analysis by the sea surface temperatures in the Asahan waters tending tolow that is in the range highest was in June namely 32,42°C -32,7°C. From theobservation the average concentration chlorophyll-a Asahan waters 2014maximum in January with an average 4,246013 mg/m3, and the lowest in Julyreached 0.913913 mg/m3. The higher sea surface temperatures henceconcentration chlorophyll-a progressively lower. In the restive of fishing groundof Asahan waters performed on highest 30,15°C -30,38°C with the lowest in therange of SST 29,68°C-29,91°C and the highest of klorofil-a 2,70164-3,0763 mg/m3 with the lowest in the range of 1,57761-1,95228 mg /m3.Keywords: Fishing Ground, Sea Surface Temperature, Klorofil-a,Aqua Modis,Asahan